2019
DOI: 10.1111/his.13862
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HSP90 associates with expression of HIF‐1α and p‐AKT and is predictive of poor prognosis in nasopharyngeal carcinoma

Abstract: Aims HSP90, as a molecular chaperone, has numerous substrate proteins, including HIF‐1α and p‐AKT, but the relationships among HSP90, HIF‐1α and p‐AKT have not been investigated in NPC. We examined and analysed the correlation between expression of HSP90, HIF‐1α and p‐AKT and clinicopathological features of NPC. Methods We collected 445 cases of NPC and 54 cases of non‐cancerous nasopharyngeal epithelia tissues, detected expression of HSP90, HIF‐1α and p‐AKT proteins in these tissues by immunohistochemistry. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…250,251 In a study of NPC epithelial tissue, high expression of HIF-1α is found to be a new independent biomarker for predicting poor prognosis in NPC patients. 252 It is found that the serum BMI-1 antibody in patients is significantly higher than in normal persons, suggesting that BMI-1 antibody may be a potential biomarker of NPC and has diagnostic and prognostic value. 253 CDH6 is overexpressed in the LMP1-positive NPC tissues, which can promote EMT and metastasis of NPC, which may be a therapeutic target of NPC.…”
Section: Radioresistancementioning
confidence: 94%
“…250,251 In a study of NPC epithelial tissue, high expression of HIF-1α is found to be a new independent biomarker for predicting poor prognosis in NPC patients. 252 It is found that the serum BMI-1 antibody in patients is significantly higher than in normal persons, suggesting that BMI-1 antibody may be a potential biomarker of NPC and has diagnostic and prognostic value. 253 CDH6 is overexpressed in the LMP1-positive NPC tissues, which can promote EMT and metastasis of NPC, which may be a therapeutic target of NPC.…”
Section: Radioresistancementioning
confidence: 94%
“…Our previous study has demonstrated that elevated expression of HSP10 protein inhibits apoptosis and associates with poor prognosis of astrocytoma, high expression of heat shock protein 10 correlates negatively with estrogen/progesterone receptor status and predicts poor prognosis in invasive ductal breast carcinoma, and high expression of HSP10 is associated with poor prognosis in oral squamous cell carcinoma 23–25. We also found that high expression of HSP90 could be used as a novel independent poor prognostic biomarker for patients with NPC 26. So far, the correlation between expression of HSP10 and HSP70 proteins and clinicopathological characteristics of NPC has not been reported.…”
Section: Introductionmentioning
confidence: 63%
“…The IHC staining for HSP10 and HSP70 in NPC samples was carried out using ready-to-use Envision TM + Dual Link System-HRP methods (Dako, Carpinteria, CA, USA). According to our laboratory experience,2326 the staining conditions for each antibody were adjusted. In brief, each section was deparaffinized and rehydrated, and high-temperature antigen retrieval was achieved for all antibodies by heating the samples in 0.01 M citrate buffer in a domestic microwave oven at full power (750 W) for 15 mins.…”
Section: Methodsmentioning
confidence: 99%
“…Positive expression of p-Akt and any positive of p-Akt/p-mTOR/ p-eIF4E were statistically higher than those in the never-smoker patients. Moreover, positive expression of p-Akt protein was more frequent in advanced NSCLC patients, while p-Akt protein was not higher in advanced stage of NPC and esophageal squamous cell carcinoma (ESCC) [32][33]. Also, NSCLC patients with positive expression of p-Akt proteins tend to have LNM and lower overall survival rates.…”
Section: Discussionmentioning
confidence: 99%